2017
DOI: 10.1016/j.ejon.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and health related quality of life in children and adolescents with cancer

Abstract: Purpose The study examined the different dimensions of fatigue (general, sleep/rest, cognitive), health related quality of life (physical, emotional, cognitive, social), and the relationships between fatigue and HRQL in hospitalized children and adolescents with cancer in Brazil. Method Participants were recruited from a pediatric oncology inpatient unit in a comprehensive cancer care hospital in southeast Brazil. They completed the PedsQL Multidimensional Fatigue Scale and the PedsQL Inventory of Quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0
19

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 70 publications
6
40
0
19
Order By: Relevance
“…We found that patients with fatigue had a lower overall QOL than those without, consistent with previous ndings (Kratz et al, 2017;Nunes et al, 2017). QOL is determined by interactions between protective factors (e.g., higher economic status) and risk factors (e.g., poor physical health) (Hatoum et al, 1998).…”
Section: Discussionsupporting
confidence: 90%
“…We found that patients with fatigue had a lower overall QOL than those without, consistent with previous ndings (Kratz et al, 2017;Nunes et al, 2017). QOL is determined by interactions between protective factors (e.g., higher economic status) and risk factors (e.g., poor physical health) (Hatoum et al, 1998).…”
Section: Discussionsupporting
confidence: 90%
“…The clinical use and assessment of the potential benefits of the complementary therapies in the treatment of cancer patients has recently increased in both pediatric (18)(19)(20)(21)(22) and adult patients (23)(24)(25)(26) . Among the manipulation practices based on the body, the therapeutic massage stands out as the most commonly used complementary therapy modality (41)(42) .…”
Section: Discussionmentioning
confidence: 99%
“…The NCCAM categorizes them mainly as: use of natural products; body and mind practices; and body-based manipulation practices (17) . Over the past three decades, the use of CTs has increased considerably both in pediatric patients (18)(19)(20)(21)(22) and in the adult population (23)(24)(25)(26) . However, the efficacy of the CTs for cancer pain management in adults with cancer in palliative care is still a gap in the scientific literature (11) .…”
Section: The National Center For Complementary Andmentioning
confidence: 99%
“…Children and parents in both countries confirmed and highlighted the major problem with fatigue and that multiple treatments generate more challenges [ 37 ]. Paediatric oncology patients all over the world have previously judged fatigue to be the most troublesome disorder [ 11 , 14 , 46 48 ]. The disease-specific rating and the multidimensional fatigue rating often have several common determinants [ 11 ].…”
Section: Discussionmentioning
confidence: 99%